2017
DOI: 10.1016/j.crci.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) chelate-bonded magnetite nanoparticles: A new magnetically retrievable catalyst for the synthesis of propargylamines

Abstract: In this study, we document the use of a reusable magnetic nanoparticle (MNP)-supported copper catalyst for the efficient synthesis of propargylamines via the A 3 coupling of benzaldehydes, phenylacetylene, and piperidine or morpholine. The new MNPs were characterized by scanning electron microscopy, energy dispersive X-ray analysis, Fourier transform infrared spectroscopy, thermogravimetric analysis, and vibrating sample magnetometry. Notably, the activity and leaching test of the catalyst indicated that the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In 2017, Sayyahi et al. successfully synthesized a copper(II) chelate‐bonded magnetite NPs through immobilization of copper(II)‐imine complex on to the surface of silica‐coated magnetite (Cu‐imine ligand@SiO 2 @Fe 3 O 4 MNPs) (Scheme ) . The as‐prepared complex shows a long‐term catalytic stability and high catalytic activity in A 3 coupling of benzaldehydes, piperidine or morpholine and phenylacetylene in the absence of solvent at 80 °C (Scheme ).…”
Section: The Various Catalytic Systems For A3 Coupling Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Sayyahi et al. successfully synthesized a copper(II) chelate‐bonded magnetite NPs through immobilization of copper(II)‐imine complex on to the surface of silica‐coated magnetite (Cu‐imine ligand@SiO 2 @Fe 3 O 4 MNPs) (Scheme ) . The as‐prepared complex shows a long‐term catalytic stability and high catalytic activity in A 3 coupling of benzaldehydes, piperidine or morpholine and phenylacetylene in the absence of solvent at 80 °C (Scheme ).…”
Section: The Various Catalytic Systems For A3 Coupling Reactionsmentioning
confidence: 99%
“…It is important to stress that despite huge advancements of the reported works in the literature, another important challenges in the A 3 coupling reactions is nature of solvent and kind of the catalyst. A number of nanocatalysts, including copper, silver, gold, nickel, magnetic nanocatalysts and Co 3 O 4 , ZnS and nanopowder zinc titanate were successfully applied for A 3 coupling reactions with yields ranging from good to excellent in appropriate times in organic solvents or aqueous medium . The authors ascribed high catalytic activity of nanocatalysts to the particles size.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…In general, several reports about propargylamine derivatives synthesis are available which in almost of them common secondary amines such as piperidine, pyrrolidine and morpholine and special conditions (high reaction temperature or long reaction time) was applied. [16][17][18][19][20][21] Imidazole have resonance electrons and it categorized as unreactive amine, therefore a few studies on the application of this substrate in this coupling reaction have been reported. We explored the generality of Co-NHC@MWCNTs and Co-NPs catalysts application with different substrate to prepare a series of propargylamine derivatives ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The results was given is Table 4. As can be [17] in water at 60°C 2 / 80 5 Cu 2 O-NPs [19] Cu (3 mol %), CH 2 Cl 2 , 60°C 5 / 92 6 Cu-NPs [18] Cu(5 mol %),solvent-free, 80°C…”
Section: Scheme 1 the Nanocatalyst Preparationmentioning
confidence: 95%
“…In view of the advantages of magnetic nanoparticles and ILs, some magnetic ILs composites have been developed [26,27]. Following our ongoing efforts for the development of more benign and efficient nanocatalysts [28][29][30][31], herein, we present the design and preparation and use of [Fe 3 O 4 @SiO 2 @(C 3 H 6 ) 2 -(Imidazolium) 2…”
Section: Introductionmentioning
confidence: 99%